Development of electrospun active films of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) by the incorporation of cyclodextrin inclusion complexes containing oregano essential oil. (November 2020) - Figueroa-Lopez, K.J.; Enescu, D.; Torres-Giner, S.; Cabedo, L.; Cerqueira, M.A.; Pastrana, L.; Fuciños, P.; Lagaron, J.M.
Abstract: This paper reports the development of biodegradable active packaging films of poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) by the incorporation of alpha- and gamma-cyclodextrins ( α -CD and γ -CDs) containing oregano essential oil (OEO). Herein, both the kneading method (KM) and freeze-drying method (FDM) were first explored for the preparation of α -CD:OEO and γ -CD:OEO inclusion complexes at host:guest ratios of 80:20 wt/wt and 85:15 wt/wt, respectively. The results showed that KM was the most efficient method for the encapsulation of OEO in the CDs cavity in terms of simplicity and rapidity, while it was also yielded the inclusion complexes with the highest antimicrobial and antioxidant performance. The α -CD:OEO and γ -CD:OEO inclusion complexes obtained by KM were thereafter incorporated at 10, 15, 20, 25, and 30 wt% into PHBV fibres by electrospinning and annealed at 160 °C to produce contact transparent films. It was observed that the optimal concentration of α -CD:OEO and γ -CD:OEO inclusion complexes for homogeneous and continuous film formation was attained at contents of 15 and 25 wt%, respectively. Higher antimicrobial and antioxidant activities were obtained for the γ-CD:OEO inclusion complexes due to the greater encapsulation efficiency of OEO in γ-CD, resulting in PHBV films with good performance for up to 15 days. This aspect, together with their improved thermal stability and mechanical strength, give interesting applications to these biopolymer films in the design of active-releasing packaging materials to maintain the physical, chemical, and microbiological characteristics of food products. Graphical abstract: Image 1 Highlights: An effective strategy was designed to obtain active food packaging films of poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV). The kneading method was the most efficient for the encapsulation of oregano essential oil (OEO) in α - and γ -cyclodextrins. The contents of α -CD:OEO and γ -CD:OEO inclusion complexes were optimal at 15 and 25 wt%, respectively. Higher active properties were attained for the films incorporating γ-CD:OEO due to their greater encapsulation efficiency. The newly developed electrospun γ-CD:OEO PHBV films showed high antimicrobial and antioxidant activities for up to 15 days.